2013
DOI: 10.1002/jsfa.6049
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alkali and oxidative treatments on the physicochemical, pasting, thermal and morphological properties of corn starch

Abstract: The results show that corn starch modified by the combined action of oxidative and alkaline treatments should be studied more, especially at the concentration limit of sodium hydroxide where gelatinization occurs. Under these conditions the effect of oxidation can be more intense and thus allow the production of starches with different properties and an increase in their industrial applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 32 publications
1
34
2
1
Order By: Relevance
“…There was no change in the morphology of the granules after modification, as obtained by Zhou et al [25] after oxidation of potato starch at low concentrations of sodium hypochlorite. Other studies reported the appearance of pores on the surface of the starch granules after the oxidation under alkaline conditions, which was not observed in this study [26].…”
Section: Morphology and Determination Of Metallic Ionscontrasting
confidence: 82%
“…There was no change in the morphology of the granules after modification, as obtained by Zhou et al [25] after oxidation of potato starch at low concentrations of sodium hypochlorite. Other studies reported the appearance of pores on the surface of the starch granules after the oxidation under alkaline conditions, which was not observed in this study [26].…”
Section: Morphology and Determination Of Metallic Ionscontrasting
confidence: 82%
“…The increased gelatinisation temperature was attributed to structural changes within the starch particles, which involved amylose-amylose and amylase-lipid interactions (Da Rosa Zavareze & Dias 2011). The higher gelatinisation temperature of starch extrudate particles was due to the reaggrangement of polymer chains into more stable configurations (Spier et al 2013). The different gelatinization temperature rise may be due to that corn starch and emulsifiers formed complexes of different type.…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 99%
“…Combined treatments generated several damages to the surfaces of the starch granules, making them more susceptible to enzymatic hydrolysis. (Spier et al, 2013) Wheat starch Chemical reactive: mixtures of i) succinic acid and acetic anhydride and ii) Azelaic acid and acetic anhydride Decreased T gel and retrogradation tendency. Increase in paste stability during storage.…”
Section: Cationic Starchmentioning
confidence: 99%